Inferior Oblique Weakening and Abnormal Head Position: Controlled Myotomy versus Recession - R. Migliorini; R. Malagola; A. M. Comberiati; L. Arrico (Journal of Ophthalmology)
Purpose. Randomized controlled trial aimed at comparing surgical outcomes in a group of patients suffering from hyperfunction of the inferior oblique (IO) muscle with abnormal head position (AHP). The surgical techniques being compared are Recession and (thread) Controlled Myotomy. Materials and Methods. The group of 20 patients suffering from medium-high hyperfunction of the IO was assessed through an ophthalmological and orthoptic examination. 10 patients underwent traditional Recession (Group  A) and 10 were treated with Controlled Myotomy (Group  B). Results. The average age was 19 years ± 10.7 SD. After 1 year, 20% of Group  A showed a small Vertical Deviation associated with a small AHP, while 80% had orthophoria and 40% of them had a small AHP. 80% of Group  B showed a small Vertical Deviation associated with an equally small AHP, while 20% had orthophoria with a full resolution of AHP. Conclusion. Based on the results obtained and the fewer intrasurgical risks involved, thread Controlled Myotomy proved to be a valid alternative to Recession. Furthermore, in case of Recession, over the long period a small residual AHP remained in the patients who had orthophoria, unlike Myotomy which led to a total resolution.